Entrepreneurial behaviour and constraints encountered by farm women in dairy enterprise - YADAV, D S; CHAHAL, V P; KUMAR, ARVIND; SINGH, UMMED (The Indian Journal of Animal Sciences, 2014)
The study analyzed various dimensions of entrepreneurial behaviour of dairy women farmers and identified their constraints encountered by them in dairy farming in Mandi district of Himachal Pradesh State of India. Performance of majority of respondents on 10 dimensions of entrepreneurial behaviour was moderate to high except in case of innovativeness and knowledge about enterprise. The overall entrepreneurial behaviour of respondents was of medium level. Except age and family size, all other personal attributes of dairy farm women were observed to be positively and significantly correlated with overall entrepreneurial behaviour. A large majority of respondents (83%) encountered medium to high extent of constraints in dairy farming. The major constraints encountered by women included lack of technical knowhow about improved technology; lack of financial institutions; difficulty in getting loan; high cost of improved milch breed, feed, concentrate and medicines; non-availability of improved seed of fodder crops; lack of proper marketing facility, lack of entrepreneurship development oriented training; low price of milk and repeat breeding in cows.